Zircon U-Pb Dating for Paragneiss in the Xinxian Area in the Dabie–Sulu Orogenic Belt and Its Geochemical Characteristics - Shaogong, Zhu; Yingjie, Liang; Yuquan, Zhang; Zian, Li (Frontiers in Earth Science, 2022)
In order to understand the subduction of the Yangtze block and its collision with the North China Craton, we performed the elements analysis and zircon U-Pb dating on paragneiss from Xinxian area, which located along the west edge of the Dabie-Sulu ultrahigh-pressure (UHP) metamorphic belt. The major elements analysis showed SiO2, Al2O3, and K2O were enriched and the rare-earth element (REE) analysis showed the paragneiss had a high content of REEs, especially light rare earth elements (LREEs). The elements analysis suggest that the protolith of paragneiss may be formed by terrestrial materials. As reflected by cathode luminescence (CL), zircon in rocks was metomorphic and had a core-edge microstructure. The edge of zircon was dated by LA-ICP-MS at 233±24Ma, which suggests that the paragneiss was formed later than the Triassic. The inherited zircon had a large age range of 456–1,727Ma, mainly in the range of 705–811Ma. The wide range of ages suggests that the protolith of paragneiss was sedimentary rocks formed no earlier than the Paleozoic.